Perbandingan Asas-Asas Hukum Pidana Umum dengan Hukum Pidana Militer pada Sistem Peradilan di Indonesia - Saskia Nursukma; Yohana Sekar Pawening; Irwan Triadi (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This study focuses on examining the comparison between the principles of general criminal law and military law applied in the justice system, through a comparative method with a normative juridical approach used as a comparative identification process of the two legal systems which includes the process of examination, trial, sentencing and consideration of legal principles. The difference in nature between general criminal law and military law is that general criminal law (Commune delicta) which anyone can carry out, is the opposite of Military Law as a special crime (Delicta proparia) which can only be carried out by certain people, in this case by a military man. Based on a literature study to see the principles of implementing the two laws, this study aims to show how the comparison of the two systems is applied, reviewing aspects of Human Rights, Justice and Legal Certainty in the legal justice system in Indonesia.